RESPON MASYARAKAT JEMUR WONOSARI TENTANG BERDIRINYA SANGGAR CANDI BUSANA PENGHAYAT KEPERCAYAAN SAPTA DARMA DITINJAU DARI SIKAP MULTIKULTURAL - Bero Santoso; Oksiana Jatiningsih (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to describe the response of the Jemur Wonosari community regarding the establishment of the Sanggar Candi Busana for followers of the Sapta Darma belief in terms of a multicultural attitude. The theory used in this study is the SOR (Stimulus-Organism-Response) theory discovered by Hovland. This theory assumes that a certain stimulus (verbal words, non-verbal cues, and symbols) will stimulate other people or groups to respond in a certain way as well. In this study using qualitative research methods with descriptive research type. The informants in this study were determined using a purposive sampling technique. The number of informants was selected with the consideration of the people living around the Sanggar Candi Busana building and also community leaders related to the activities of the Sapta Darma belief system until data saturation was obtained. The informants in the study found ten informants consisting of the community, community leaders in the Jemur Wonosari sub-district, and religious leaders of the Sapta Darma belief. The location in this study was in the Jemur Wonosari sub-district, Wonocolo District, Surabaya City. Data collection techniques used were in-depth interviews and observation. The results of this study indicate that the residents of Jemur Wonosari gave two responses, namely, the response before the public knew the function of the Fashion Temple Studio. And the positive response to the existence of the Sanggar Candi Busana and adherents of the Sapta Darma belief, community members live side by side. Acceptance of community members is part of humanist communication, Sapta Darma activities which involve the community as a form of upholding the value of harmony. A multicultural attitude emerges where society maintains harmonious relations and provides space for differences in belief and worship without disturbing or disturbing.